A case of jejunal perforation secondary to jejunal diverticulosis in a patient with COVID-19 pneumonia - Sharma, Varsha A.; Kamat, Manmohan M.; Sathyan, Jeena K.; Barman, Seema; Shetye, Shravani (International Surgery Journal, 2021)
Jejunal diverticulitis is a rare disease, with jejunal perforation as its rarest complications due to low intraluminal pressure. Since the current pandemic of COVID-19 it has shown to be affecting gastrointestinal system in a proportion of patients, and worsening of pre-existing GI conditions. We encountered a case of a 75 years old gentleman, suffering with severe COVID-19 pneumonia, who during the course of the disease presented with spontaneous Jejunal perforation, secondary to jejunal diverticulosis. Jejunal diverticula are the least common type of small bowel diverticula & perforation as their complication is the rarest of all complications. Their presentation is variable from asymptomatic to chronic abdominal symptoms and the complications such as perforation as described in our case. Their relative clinical rarity and varied presentation may make diagnosis both delayed and difficult.